Periapical lesion treatment with retrograde filling and bone graft. A case report - Jarrín Peñafiel, María José (2019)
The aim of this study is to present a case in which after the endodontic treatment failed, a cystic lesion was observed in periapical area. The present case concerns a 39 years old female patient without relevant medical history, attended SERODU dental clinic, on clinical examination during the palpation the presence of a soft consistency tumefaction that would be affecting the integrity bone tissue, without symptomatology. The pulp vitality tests turned out to be negative. A radiolucidal shadow compatible with chronic periapical lesion affecting 11 and 12 teeth was observed during the radiographic examination. So it was decided to perform periapical surgery with apicectomy, apical retrograde filling and cystic injury enucleation, followed by guided bone regeneration. At three months of control, radiographically a radiopaque area compatible with bone regeneration was found with a radiolucid halo separating with the original basal bone, and at six months, complete bone regeneration was observed. The retrograde filling and bone grafting technique is an effective treatment technique for apical canal sealing and regeneration of large periapical defects.